Umat Katolik Sumba di Tengah Himpitan Tradisi dan Kepercayaan Marapu: Menyimak dan Menemukan Upaya Pastoral untuk Menumbuhkan Pengetahuan Iman Umat Katolik Sumba - Si, Stefanus; Panda, Herman Punda; Sudiharsa, Raymundus I Made (Media: Jurnal Filsafat dan Teologi, 2024)
The article discusses the pastoral challenges of the Sumba Catholic Church regarding the Catholics who still maintain their cultural traditions, namely the Merapu culture. This group of Catholics seems to be in a crush of culture and the Catholic faith. By using qualitative research methods, this paper aims to identify the pastoral problems faced by Catholics bound by the Merapu tradition, and then find appropriate pastoral solutions for the development of the Catholic faith. The author found that the fundamental pastoral problem is the lack of understanding of the Catholic faith among this group of people. Therefore, the author offers pastoral solutions to this problem, such as increasing the catechesis of the people, empowering the family as the first school of faith, and strengthening reliable lay pastoral ministers. In addition, inculturation of the Catholic faith plays an important role in strengthening the Catholic faith without uprooting them from their cultural roots.